2013
DOI: 10.1080/1068316x.2013.770856
|View full text |Cite
|
Sign up to set email alerts
|

Framing and perceptions of stalking: the influence of conduct severity and the perpetrator–target relationship

Abstract: Research has demonstrated that the way in which questions are presented (i.e., framed) has the capacity to influence responses to subsequent questions (Tourangeau & Rasinski, 1988).In the context of stalking, perception research has often been framed in terms of whether or not particular behaviours constitute stalking. The current research investigates whether the framing of the opening question (question frame), conduct severity and the perpetrator-target relationship influence perceptions of stalking. Two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…The term ‘harassment’ was employed as opposed to ‘stalking’ as this is the term employed by English police officers following the dictates of the Protection from Harassment Act (). It is worth noting that a recent study found that the framing of repetitive behaviour as either ‘harassment’ or ‘stalking’ did not influence perceptions of stalking using four of the five scale items used in the current work (Scott, Rajakaruna, & Sheridan, ). The scale items have been employed in previous works (e.g., Scott & Sheridan, ; Scott & Tse, ; Scott et al ., , ); while the vignettes were developed following a review of vignettes employed in recent works (e.g., Scott & Gavin, ; Scott & Sheridan, ; Scott et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…The term ‘harassment’ was employed as opposed to ‘stalking’ as this is the term employed by English police officers following the dictates of the Protection from Harassment Act (). It is worth noting that a recent study found that the framing of repetitive behaviour as either ‘harassment’ or ‘stalking’ did not influence perceptions of stalking using four of the five scale items used in the current work (Scott, Rajakaruna, & Sheridan, ). The scale items have been employed in previous works (e.g., Scott & Sheridan, ; Scott & Tse, ; Scott et al ., , ); while the vignettes were developed following a review of vignettes employed in recent works (e.g., Scott & Gavin, ; Scott & Sheridan, ; Scott et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…Rather than scale development, community surveys more commonly employ short vignettes and seek to establish participants perceptions of stalking with respect to key areas of interest (seriousness and gender-based differences for example). Within this well-established sub-field, several studies emerge as highly influential, such as by Scott and colleagues (Scott & Sheridan, 2011;Scott, et al, 2010Scott, et al, , 2014, Sheridan (Sheridan et al, 2001(Sheridan et al, , 2002, Dennison (Dennison, 2007;Dennison & Thomson, 2000, and Dunlap and colleagues (Dunlap et al, 2012).…”
Section: Attitudinal Support For Stalkingmentioning
confidence: 99%
“…Based on existing studies, some relevant factors regarding the perception of stalking have emerged, including the previous relationship between stalker and victim (Scott, Lloyd, & Gavin, 2010;Scott & Sheridan, 2011;Sheridan & Davies, 2001b;Weller et al, 2013), gender (Dennison & Thomson, 2002;Phillips, Quirk, Rosenfeld, & O'Connor, 2004;Scott & Sheridan, 2011;Sheridan, Gillett, Davies, Blaauw, & Patel, 2003;Sinclair, 2012), persistence (Dennison, 2007;Dennison & Thomson, 2002;Scott & Sheridan, 2011), and presence of threats and level of fear or distress (Dennison & Thomson, 2002;Hills & Taplin, 1998;Phillips et al, 2004;Scott, Rajakaruna, & Sheridan, 2014;Sheridan et al, 2003). In contrast, respondents' personal experiences of stalking do not appear to influence their sensitivity, attitudes, or evaluation of harassment behaviors (De Fazio & Galeazzi, 2004;Phillips et al, 2004).…”
mentioning
confidence: 99%